Psychological readiness of athletes to return to play following injury - Monahan, A. C.; Hunt, T. N.; Harris, B. S.; Mutchler, J.; Memphis, T. N. (Journal of Athletic Training, 2019)
Context: Return to play decisions made without the assessment of an athlete`s psychological readiness could lead to athletes being returned to play before psychologically ready. Returning an injured athlete to sport before they are both physically and psychologically ready can lead to increased or prolonged psychological concerns, fear-avoidance behavior and higher risk of re-injury. The purpose of this study was to investigate the psychological readiness and fear-avoidance of student-athletes to return to play following injury. We hypothesized hat among student-athletes currently returning to play, some athletes would not be psychologically ready to return. We also hypothesized that if there were student-athletes who were not psychologically ready, those athletes would have higher fear avoidance compared to those who were psychologically ready. Methods: Thirty-four Division I student-athletes (20 males, 14 females; 19.76 ± 1.42 years old) volunteered to participate in the cross-sectional study. All participants were returning to play following injury that resulted in at least one missed practice or competition. Within 24 hours of return to play, as decided by each athlete`s Athletic Trainer, the participants completed the Injury-Psychological Readiness to Return to Sport Scale (I-PRRS), and the Athlete Fear Avoidance Questionnaire (AFAQ). None of the investigators were involved in return to play decisions. Both questionnaires ave been previously assessed for acceptable reliability and validity for use with sport-related injury. A cut-off of 50 on the I-PRRS was used to determine psychological readiness, based on previous literature that a score of 50 indicates the athlete is highly confi dent to return to play. Participants were placed into two groups: I-PRRS scores > 50 = Ready, and I-PRRS scores < 50 = Not Ready. An independent t-test was used to compare AFAQ scores between groups. Signifi cance level was set to p < 0.05, and effect size was calculated. Results: Of the 34 participants, 17 scored into the Ready group (mean I-PRRS = 55.76 ± 2.75), and 17 scored into the Not Ready group (mean I-PRRS = 38.12 ± 6.42). The Ready group reported signifi cantly less fear avoidance as compared to the Not Ready group (Ready: 14.76 ± 3.75, Not Ready: 22.59 ± 8.71; p = 0.003; ES = 0.89). Observed statistical power was 81% for the difference in AFAQ scores between groups. Conclusions: The results of this study suggest not all athletes returning to play are highly confi dent in their ability to return to play. Athletes whom lack confidence in returning to their sport may experience higher fear avoidance that could go undetected by the Athletic Trainer if not assessed prior to return to play. The assessment of psychological readiness and fear avoidance should be completed prior to returning an athlete to their sport in order to appropriately address any concerns.